Zideologizowanie przekazu prasy radykalnych ruchów społecznych w kontekście tabloidyzacji mediów (przykład prasy ruchu anarchistycznego) - Malendowicz, Paweł (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
The anarchist movement, aiming to remove all ruler – ruled relations, is a radical social movement. The movement has its own means of communication. The phenomenon of tabloidization, understood as the propagation of properties typical of tabloid media, concerns the anarchist press as well, but only marginally. It is manifested by the ideologization of the content of this press. The communications of the anarchist movement are directed at its social surroundings and also occur within the movement. Tabloidization is an ineffective means of achieving an intangible benefit (winning supporters for the movement). The tabloidization of the message aimed at obtaining a benefit is only meaningful in the internal communications, where it helps maintain the headcount on account of the ideologization, simplification and sensational character of the message. While criticizing the tabloidization of traditional media, anarchists have developed their concepts using simplified messages for the purpose of social mobilization, riots and future insurrections. In these concepts, shallow messages referring to irrational human emotions become a source of revolutionary attitudes.